LOW-TEMPERATURE PLASMA DECOMPOSITION OF LIQUIDS UNDER ULTRASONIC ACTION - Garibyan, Boris; Kohlert, Victoria (Revista Inclusiones, 2020)
In this work, a low-temperature plasma initiated in liquid media between electrodes has been shown to be able to decompose hydrogen containing organic molecules leading to obtaining gaseous products with volume part of hydrogen higher than 90% (up to gas chromatography data). Preliminary evaluations of energetic efficiency, calculated from combustion energy of hydrogen and initial liquids and electrical energy consumption have demonstrated the efficiency about 60-70% depending on initial liquids composition. Theoretical calculations of voltage and current values for this process have been done, that is in good agreement with experimental data.